Tunable Nanostructured Coating for the Capture and Selective Release of Viable Circulating Tumor Cells. (15th January 2015) - Reátegui, Eduardo; Aceto, Nicola; Lim, Eugene J.; Sullivan, James P.; Jensen, Anne E.; Zeinali, Mahnaz; Martel, Joseph M.; Aranyosi, Alexander J.; Li, Wei; Castleberry, Steven; Bardia, Aditya; Sequist, Lecia V.; et al.
<x xml:space="preserve">Abstract</x> A layer‐by‐layer gelatin nanocoating is presented for use as a tunable, dual response biomaterial for the capture and release of circulating tumor cells (CTCs) from cancer patient blood. The entire nanocoating can be dissolved from the surface of microfluidic devices through biologically compatible temperature shifts. Alternatively, individual CTCs can be released through locally applied mechanical stress. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>